Listy Romana Pollaka do Natalii Tułasiewicz (1942–1943) - Ćwiklińska, Zuzanna; Lewandowska, Agata; Tyl, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article is an editorial work that includes twelve letters written by professor Roman Pollak to his former student, Natalia Tułasiewicz, during World War II, which are currently part of the Tułasiewicz Family Archive in Poznan. The introduction summarises Tułasiewicz’s biography and describes her relationship with the professor; during the war, they both left Poznan and lived in a number of places, attempting to maintain the relationship. The article also concisely outlines the history of the University of the Western Lands in which Roman Pollak was involved at the time of his correspondence with Natalia Tułasiewicz.